RANCANGAN MEDIA KOMUNIKASI VISUAL PROMOSI PRODUK KERAJINAN ROTAN DESA TERENTANG KABUPATEN BANGKA BARAT - Mohammad Reza Baskara; Mukhsin Patriansyah; Husni Mubarat (UNIVERSITAS INDO GLOBAL MANDIRI, 2017)
Visual Media Media Design The Rattan Product of Rattan Terentang aims to introduce and market the existing rattan handicraft products in the Terentang Village. The purpose of introducing in this case is to provide information to the community about the existence of the Terentang Village in West Bangka Regency as a village of rattan craftsmen, unique rattan products, and local wisdom of rattan craftsmen from the Terentang Village regarding the use of rattan plants and rattan cultivation. Marketing of rattan products from Desa Terentang through the design of visual communication media aims to sell products to a wider market share with the design of the website as the main media as well as other supporting media that serves to direct the target audience to the website page www.rotanterentang.com address. Key words: Visual Communication Media, Website, Rattan Craft Product, Outlying Village, West Bangka Regency